Challenges and achievements of the implementation of interactive groups in a learning community - Villarreal-Yazán, Bolívar (2021)
The present research was born from the need to evaluate the achievements and challenges regarding the implementation of a new educational methodological strategy proposed in Ecuador. The objectives were: 1) To evaluate the application of Interactive Groups as a methodological strategy for learning. 2) To determine the difficulties faced by the institution in the implementation phase. 3) To establish what has been achieved. This descriptive and qualitative work considers the Antisana Educational Unit as a case study, an institution located in a rural context in Ecuador. The applied research instruments were a semi-structured interview with the rector and focus groups with teachers, students and volunteers. The areas of investigation converged on institutional administrative management, teacher qualities, application of the interactive group methodology, and volunteer performance. The main achievements were egalitarian dialogue, transformation and solidarity, as principles of dialogic learning, in addition to student leadership and the empowerment of the area of proximate development. Difficulties were noted in some students, teachers and volunteers evidenced in the lack of empowerment, superficiality of instrumental activities and low participation, respectively. The challenges generated from this first experience revolve around the consolidation of the strategy through the internalization of the interactive groups approach. It is necessary to propose collaborative activities and to integrate other social actors as volunteers. Aspects that will strengthen social inclusion and cohesion.